2010
DOI: 10.1111/j.1365-2702.2010.03420.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an individualised education programme on asthma control, inhaler use skill, asthma knowledge and health‐related quality of life among poorly compliant Korean adult patients with asthma

Abstract: This study confirmed the importance of education for patients suffering from asthma in managing their symptoms and promoting their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
2
24
0
3
Order By: Relevance
“…Most intervention studies that aimed to increase medication adherence in adults with asthma found that better medication adherence predicted increases in QOL from baseline to follow-up at 2 to 4 weeks [12], and even over longer periods of time, like 3 months [13]. However, some studies did not show improvement in QOL as a result of better medication adherence at 3 or 6 months after the intervention [14].…”
Section: Introductionmentioning
confidence: 94%
“…Most intervention studies that aimed to increase medication adherence in adults with asthma found that better medication adherence predicted increases in QOL from baseline to follow-up at 2 to 4 weeks [12], and even over longer periods of time, like 3 months [13]. However, some studies did not show improvement in QOL as a result of better medication adherence at 3 or 6 months after the intervention [14].…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the main effects of each of time alone, group alone Asthma education program, however, yielded variable results in previous studies. Choi and Chung [48] conducted study to examine the effect of an individualized education programme on asthma control, inhaler use skill, asthma knowledge and health-related QoL (HRQoL) among poorly compliant adult Korean patients with asthma. Their study results showed that peak expiratory flow rate, inhaler using skill scores and health-related quality of life scores improved following the intervention, whereas knowledge score did not.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found that the patients in the experimental group had higher inhaler use skill mean scores after training compared to the control group. In a study by Choi and Chung (16), it was determined that the level of inhaler use skills significantly improved after individual training. In a study by Kishan and Garg (17), it was reported that after a period of 3 months following asthma training, the rate of accurate inhaler use increased from 44% to 86% in elderly patients and increased from 64% to 98% in young individuals.…”
Section: Discussionmentioning
confidence: 99%